Energy-Efficient Source Authentication for Secure Group Communication with Low-Powered Smart Devices in Hybrid Wireless/Satellite Networks. (28th September 2010) - Roy-Chowdhury, Ayan; Baras, John S.
Abstract : We describe a new class of lightweight, symmetric-key digital certificates called extended TESLA certificates and a source authentication protocol for wireless group communication that is based on the certificate. The certificate binds the identity of a wireless smart device to the anchor element of its key chain; keys from the chain are used for computing message authentication codes (MACs) on messages sourced by the device. The authentication protocol requires a centralized infrastructure in the network: we describe the protocol in a hybrid wireless network with a satellite overlay interconnecting the wireless devices. The satellite is used as the Certificate Authority (CA) and also acts as the proxy for the senders in disclosing the MAC keys to the receivers. We also design a probabilistic nonrepudiation mechanism that utilizes the satellite's role as the CA and sender proxy. Through analysis, we show that the authentication protocol is secure against malicious adversaries. We also present detailed simulation results that demonstrate that the proposed protocol is much cheaper than traditional public key-based authentication technologies for metrics like processing delay, storage requirements, and energy consumption of the smart devices.